FENOMENA TARI KONTEMPORER DALAM KARYA TARI - Indrayuda – (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2010)
The aim of this articel is to reveal the contemporary phenomenom of the dance work of the student of Sendratasik UNP and STSI Padang Panjang through last assignment. This research is focused on the phenomenom and student’s tendency on creating the dance work on a contemporary form. The research method used is descriptive qualitative and for the main instrument is the researcher himself. The collection of data dance through observation, interview and collecting the related literature. The analysis of the data done through conventional analysis. The result of the research shows that there is a tendency from the student on creating each of their work for the last assignment by using contemporary model, such as an the pattern of work, the type of dance, the form of performance and the orientation of creation. The growth of this sympton is caused from high frequency of the student to be involved in many forums of contemporary dance, and thruogh the appreciation of lecturer’s figur and work. This research can be concluded that the sympton and tendency of contemporary is appeared in the student’s dance work because of: 1) the influence of the lecturer, 2) the influence of dance forum, 3) the influence of dance work of the artists of West Sumatera and 4) the freedom given to the students. It is essential to be suggested from this articel so that there is correct guide from the lecturer available of Sendratasik FBSS UNP and STSI Padang Panjang to pay attention for the monumental dance learning, so that the balance is created on the dance learning in academic field. ABSTRAK Tulisan ini bertujuan mengungkap fenomena karya tari kontemporer dari mahasiswa Sendratasik UNP dan STSI Padang Panjang dalam tugas akhir. Penelitian ini difokuskan pada fenomena kecenderungan mahasiswa dalam menciptakan karya tari dalam bentuk kontemporer. Penelitian ini menggunakan metode deskriptif kualitatif dengan instrumen utama adalah peneliti sendiri. Pengumpulan data dilakukan melalui metode observasi, wawancara, dan studi kepustakaan. Data dianalisa secara konvensional. Hasil penelitian menunjukkan ada kecenderungan mahasiswa menciptakan karya mereka dalam tugas akhir (TA) dengan model kontemporer, seperti pada pola tarian, tipe tarian, bentuk pertunjukan, dan orientasi tarian. Pertumbuhan gejala ini disebabkan frekuensi yang tinggi dari mahasiswa untuk terlibat dalam berbagai forum tarian kontemporer dan apresiasi terhadap figure dan karya dosen. Kesimpulan penelitian adalah gejala dan kecenderungan karya kontemporer muncul dalam karya mahasiswa karena 1) pengaruh dosen, 2) pengaruh forum tarian, 3) pengaruh karya tari artis-artis Sumatera, dan 4) kebebasan yang diberikan kepada mahasiswa. Dari penelitian ini sangat disarankan agar ada pedoman yang benar dari dosen Sendratasik FBSS UNP dan STSI Padang Panjang agar memperhatikan dasar-dasar pembelajaran tari sehingga ada keseimbangan pembelajaran tari dalam dunia akademis.